Testing of wear in contact with strenx 700 and autofretted steel - Simonović, Milan; Džunić, Dragan; Mitrović, Slobodan (Journal of Production Engineering, 2020)
This paper presents an experimental test of contact wear between STRENX 700 material and autofretched steel, which is obtained in practice through the autofretching (material reinforcement) of artillery pipes. Three types of lubricants were used during the test: HD 46 oil, Hysol T15 emulsion, and For 3 grease. The experiment was conducted by varying three values of the normal load: 10, 20, and 30 N, as well as two values of the disk rotation speed: 0.5 and 1 m/s. The test was performed using a tribometer "TR – 95," which operates based on a block-on-disk configuration. The "ASTM G 77" standard was employed for testing. The metallurgical optical microscope "MEIJI MT8500" was used to capture images of the wear marks. The purpose of the test was to determine the most suitable method of lubricating the contact between the materials used. Through a comparative analysis of the results, it was concluded that the emulsion is the most suitable means of lubricating the contact between the materials used, as it resulted in very low material consumption under all test conditions.